2017
DOI: 10.13005/ojc/330528
|View full text |Cite
|
Sign up to set email alerts
|

New Analytical HPLC Method Development and Validation for the Simultaneous Quantification of Paritaprevir Ombitasvir and Ritonavirin Spiked Human Plasma.

Abstract: A rapid HPLC bio-analytical method has been developed and validated for the simultaneous quantification of Ombitasvir (OMBTSR), Ritonavir (RTNVR), Paritaprevir (PTVR) in human plasma. OMBTSR and PTVR are used to control Hepatitis-C infection. RTNVR is used in the treatment of HIV/AIDS. The method was developed with Column (Intersil ODSC 18, 250 mm × 4.6 mm × 5µ) at 230 nm wave length and at flow rate of 1.0 mL/min. The mobile phase consisted of 20% Acetonitrile, 20% Methanol, 60% 1mM NH 4 H 2 PO 4 Buffer(P H 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Literature review revealed that few methods were reported for the simultaneous determination of OMB, PAR, and RIT, all based on chromatographic analysis techniques. Eight papers described High Performance Liquid Chromatography (HPLC) methods using isocratic mobile phase 6–13 and two Ultra‐High Performance Liquid Chromatography (UHPLC) methodologies were reported utilizing MS/MS detection 14,15 . No UV spectroscopic methods were reported for the simultaneous determination of the three antiviral drugs under study.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review revealed that few methods were reported for the simultaneous determination of OMB, PAR, and RIT, all based on chromatographic analysis techniques. Eight papers described High Performance Liquid Chromatography (HPLC) methods using isocratic mobile phase 6–13 and two Ultra‐High Performance Liquid Chromatography (UHPLC) methodologies were reported utilizing MS/MS detection 14,15 . No UV spectroscopic methods were reported for the simultaneous determination of the three antiviral drugs under study.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only four research methods were reported using HPLC. Three methods used acetonitrile (ACN) as organic modifier in proportion higher than 60% in the isocratic mobile phase [6, 7, 8] and one method used a 40% combination of methanol and ACN as organic modifier [9]. Two UHPLC methods were reported using MS/MS detection [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of studied drugs is not listed in any pharmacopoeia. Literature survey revealed that there are only two number of HPLC methods for the quantification of selected drug combination [9,10]. An RP-HPLC method for the determination of ombitasvir, paritaprevir and ritonavir in bulk and its dosage forms was presented by Srinivas and Yadagiriswamy [9].…”
mentioning
confidence: 99%
“…The retention times for ombitasvir, paritaprevir and ritonavir were 2.315 min, 2.89 min and 5.483 min, respectively. Phani et al [10] determined ombitasvir, paritaprevir and ritonavir in spiked human plasma by HPLC with UV detection at 230 nm using an Intersil ODS C18 analytical column and a mobile phase consisting of acetonitrile, methanol, 1 mM NH4H2PO4 buffer (20:20:60 v/v/v, pH 6.5). The retention times of ritonavir, ombitasvir and paritaprevir are 5.7 min, 7.8 min and 12.8 min, respectively.…”
mentioning
confidence: 99%